Design of an IoT-Based Snack Vending Machine with QR Code Payment, Automatic Stock Monitoring, and QoS Evaluation - Berlina Putri Agustine; I Gede Puja Astawa; Anang Budikarso (The Indonesian Journal of Computer Science, 2026)
The rapid advancement of the Internet of Things (IoT) has enabled the development of smart vending systems with advanced automation and monitoring capabilities. This study details the design and implementation of an IoT-based snack vending machine that incorporates QR code payment, automated stock monitoring, and network Quality of Service (QoS) assessment. The system employs embedded devices and wireless communication to manage transactions, monitor inventory levels in real time, and enable remote supervision. QR code–enabled digital payment is adopted to enhance transaction efficiency and user convenience, while quality of service metrics are evaluated to assess network performance and system reliability. Experimental findings indicate that the system operates reliably, delivers precise stock information, and maintains stable network performance under standard operating conditions. These results suggest that the proposed solution is both practical and effective for smart vending applications and is adaptable to other IoT-based automated service systems.